Urine as a Biobased Fertilizer: The Netherlands as Case Study - Beijer, S.; Das, S.; Helmus, R.; Scheer, P.; Jansen, B.; Slootweg, J. C. (Sustainability & Circularity NOW, 2024)
Humankind has grown increasingly dependent on mineral fertilizer to feed a growing world population. However, nutrients are rarely recovered and recycled after consumption, leading to environmental waste issues now and potential supply issues in the future. Urine is rich in these nutrients and is therefore a prime candidate as a precursor for biobased fertilizers. This work presents a case study to remove potentially present contaminants from human urine using activated carbon adsorbents to adhere to Dutch fertilizer legislation. In the urine, three pharmaceuticals were identified by target analysis and 11 other contaminants by suspect screening using liquid chromatography quadrupole time-of-flight mass spectrometry (LC-QTOF/MS). These were successfully removed by treatments with both granulated and powdered activated carbon, albeit with a loss of 16–17% and 2–4% of dissolved nutrients, respectively. Further screening of inorganic contaminants and persistent organic pollutants by inductively coupled plasma mass spectrometry (ICP-MS) and gas chromatography quadrupole-Orbitrap mass spectrometry (GC-Q-Orbitrap/MS) showed that all prerequisites for fertilizer status are met, paving the way for its future legal use as a biobased fertilizer in the Netherlands.
Keywords: Nutrient recycling; Biobased fertilizer; Activated carbon adsorbent; Pharmaceutical removal; Fertilizer legislative framework; Target analysis; Suspect screening